The application and deployment of welfare technology in Swedish municipal care: a qualitative study of procurement practices among municipal actors - Sanna Kuoppamäki (BMC, 2021)
Abstract Background Welfare technology has been launched as a concept to accelerate digital transformation in care services, but the deployment of these technologies is still hindered by organisational resistance, lack of infrastructure, and juridical and ethical issues. This paper investigates decision-making among municipal actors in the application and deployment of welfare technology from a procurement process perspective. The study explores the perceptions and negotiations involved in purchasing welfare technology at each stage of the procurement model, revealing the impact of technical, economic, juridical and ethical competence on the mapping, planning, procurement, implementation and management of welfare technology. Methods The study presents empirical findings from qualitative interviews conducted among municipal actors in Sweden. Semi-structured interviews were gathered in 2020 among procurement managers, IT managers, and managers in social administration in three different municipalities (n = 8). Content analysis and systematic categorisation were applied resulting in the division of procurement practices into sub-categories, generic categories and main categories. Results Challenges in the application and deployment of welfare technology occur at all stages of the procurement model. In mapping and planning, barriers are identified in the need analysis, requirement specification and market analysis. In the procurement stage, economic resources, standardisation and interoperability hinder the procurement process. Implementation and management are complicated by supplier assessment, legislation, cross-organisational collaboration and political strategy. Building on these findings, this study defines 'procurement competence' as consisting of technical, economic, juridical and ethical expertise in order to assess and evaluate welfare technology. Technical and ethical competence is needed in early stages of procurement, whereas juridical and economic competence relates to later stages of the model. Conclusions Procurement competence is associated with the application and deployment of welfare technology in (1) assessment of the end-user's needs, (2) estimation of the costs and benefits of welfare technology and (3) management of juridical and legislative issues in data management. Economic and juridical decisions to purchase welfare technology are not value-neutral, but rather associated with socially shared understandings of technological possibilities in care provision. Optimisation of procurement processes requires a combination of capabilities to introduce, apply and deploy welfare technology that meets the demands and needs of end-users.